VOICES OF WOMEN LIVING WITH HIV/AIDS FROM PUNJAB - Gaur, Gaurav (Journal of Social Work Education and Practice, 2023)
There are many attempts made to understand the problems of People Living with HIV/AIDS around the world, and to highlight the life lived by them. In this paper, an effort has taken to highlight the problems faced by the HIV/AIDS infected women in the state Punjab, India. An exploratory design has been adopted for the study to examine the situation in which these women were surviving. Interview method was used to collect data. In all the cases, these women got the virus from their husbands and the results suggest that they were living an ostracized life. Their innocence and commitment to relationship is obvious from the fact that they continue to live with their partner. Due to illiteracy and poverty, they were living a miserable life.
Keywords: Women; HIV/AIDS; Gender; Socio-economic Status; Problems